Informal Introduction to Stochastic Processes with Maple - Vrbik, Jan; Vrbik, Paul (Universitext, 2013)
The book presents an introduction to Stochastic Processes including Markov Chains, Birth and Death processes, Brownian motion and Autoregressive models. The emphasis is on simplifying both the underlying mathematics and the conceptual understanding of random  processes. In particular, non-trivial computations are delegated to  a computer-algebra system, specifically Maple (although other  systems can be easily substituted). Moreover, great care is taken to  properly  introduce the required mathematical tools (such as  difference  equations and generating functions) so that even students  with only  a basic mathematical background will find the book  self-contained.  Many detailed examples are given throughout the text  to facilitate  and reinforce learning.  Jan Vrbik has been a Professor of Mathematics and Statistics at Brock University in St Catharines, Ontario, Canada, since 1982. Paul Vrbik is currently a PhD candidate in Computer Science at the University of Western Ontario in London, Ontario, Canada.